ANALISA PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAAN PENUTUP ATAP - Mulyadi, Mulyadi; Hasnawati, Hasnawati (Universitas Bengkulu, 2019)
Productivity is one of the important factors in determining the success of a construction job. Increased productivity will reduce work time, and that will reduce costs. In general, the value of productivity is determined by factors in the amount of work volume, time of implementation, and the number of workers. In order for the work to be completed properly, planning efforts are needed by taking into account these factors. For this reason, this study was conducted to determine the value of productivity in one of the components of building work, namely roof cover work. The objects studied were the work of installing roof coverings and the installation of 4 (four) project locations, namely the 4 x 25 Shophouse Construction Project in Meulaboh West Aceh, Building of the Rector & Administration Bureau of STKIP Building Nation Getsempena Banda Aceh, Construction of the Getsempena STIKes College Building Lhoksukon North Aceh and Construction of the East Aceh Bina Nusantara Idi STIKes Building. Roof material using zincalume material. The roof work volume is planned to be 2022.38 m2. The research was conducted through field observations by recording the work volume directly, the duration of each stage of work, and the number of workforce involved. The results of the analysis show that the productivity value for roofing work is obtained at 12,061 m2/hour or 96,487 m2/day and for roof joint installation work is obtained at 13,926 m / hour or 111,405 m/day.